Pengaruh Iklim Organisasi dan Disiplin Kerja Terhadap Kinerja Pegawai PT. Dinamika Airufindo Persada Jakarta Dengan Pengawasan Sebagai Mediator - Eric Hernawan (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2022)
To investigate the performance of employees of PT. The dynamics of Airufindo Persada Jakarta used three independent variables of organizational atmosphere, work discipline and supervision by determining the indirect effect of organizational atmosphere and work discipline on employees of PT. Dynamics of Airufindo Persada. These two indirect effects can be determined by determining the direct effect of organizational atmosphere, work discipline and supervision on the work discipline of PT. The dynamics of Airufindo Persada and the direct influence of organizational atmosphere and work discipline partially on supervision. The method used is a quantitative method with a descriptive type of research to determine the simple regression equation and multiple regression from 82 respondents employees of PT. Dynamics of Airufindo Persada Jakarta. The regression equation was determined after the research data were tested with validity, reliability, normality, multicollinearity and heteroscedasticity tests. The investigation of the positive and significant effect was carried out by determining the t-test (tcount>ttable) for simple regression and the F-test (Fcount>Ftable) for multiple regression. In this study, all direct and indirect effects were positive and significant. The influence of the independent variables of organizational atmosphere, work discipline and supervision in percent are 27.3%, 25.7% and 23.3%. This effect is true because all Fcount>Ftable (30.006, 27.715 and 24.332>3.57). The effect of organizational atmosphere and discipline partial employment of supervision in percent are 26.3% and 54.2%. This effect is true because all Fcount>Ftable (28,563 and 94,554 > 3.57).